An Investigation into Student Engagement in Higher Education Classrooms - Paula Witkowski, PhD; Thomas Cornell, PhD (Park University, 2017)
This article reports on a one-year research project that used peer coaching and collaboration between two reading professors to study the effects of collaborative classroom activities on student engagement. In order to address professors' concerns about student participation, two undergraduate reading-methods classes were revised through the inclusion of more collaborative learning activities. Classroom observations were conducted to take notes on both pedagogical methods and student response to these methods. Students were also asked to self-assess their engagement in behavioral, cognitive, and affective domains. The results of this research were then used to revise pedagogical techniques in these and other classes.